Bis 4-(dimethylamino)pyridinium tetrabromidobis(4-chlorophenyl)stannate(IV)-4-bromochlorobenzene (1/1) - Lee, S.M.; Robinson, W.T.; Ali, Hapipah Mohd; Lo, K.M. (International Union of Crystallography, 2009)
In the title compound, (C7H11N2)(2)[SnBr4(C6H4Cl)(2)]center dot-C6H4BrCl, the Sn-IV atom in the tetrabromidobis(4-chlorophenyl)stannate(IV) anion lies on a centre of inversion. The distances between the 4-(dimethylamino)pyridinium N atom and the Br atoms of the anion are 3.450 (2) and 3.452 (2) angstrom, suggesting weak hydrogen bonding. The 4-bromochlorobenzene solvent molecule, which is a bromination by-product from the reaction, is disordered about a twofold rotation axis with approximately equal occupancy.